2008
DOI: 10.1088/0957-4484/19/32/325704
|View full text |Cite
|
Sign up to set email alerts
|

Effect of structure, particle size and relative concentration of Eu3+and Tb3+ions on the luminescence properties of Eu3+co-doped Y2O3:Tb nanoparticles

Abstract: Eu(3+) co-doped Y(2)O(3):Tb nanoparticles were prepared by the combustion method and characterized for their structural and luminescence properties as a function of annealing temperatures and relative concentration of Eu(3+) and Tb(3+) ions. For Y(2)O(3):Eu,Tb nanoparticles annealed at 600 and 1200 °C, variation in the relative intensity of excitation transitions between the (7)F(6) ground state and low spin and high spin 4f(7)5d(1) excited states of Tb(3+) is explained due to the combined effect of distortion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 27 publications
(26 reference statements)
7
62
0
Order By: Relevance
“…Terbium ions are the most important green-emitting luminescent activators for several phosphors [11][12][13] because it has a sharp emission around 544 nm with high intensity, which is close to the theoretical optimum wavelength for the green component of three primary color centers. Ce 3+ is also a widely used luminescence activator in optical materials and its properties are well known.…”
Section: Introductionmentioning
confidence: 64%
“…Terbium ions are the most important green-emitting luminescent activators for several phosphors [11][12][13] because it has a sharp emission around 544 nm with high intensity, which is close to the theoretical optimum wavelength for the green component of three primary color centers. Ce 3+ is also a widely used luminescence activator in optical materials and its properties are well known.…”
Section: Introductionmentioning
confidence: 64%
“…3. Bare NCs showed characteristic Y-O bond vibrations of YO 6 polyhedra at w562 cm À1 [42]. Probably owing to the very low concentration of dopant ions in the lattice (max w2 mol%), the vibrational features related to Eu-O and Gd-O was not registered.…”
Section: Conjugation Of Yo Ncs With Folic Acid Through Polycation Gramentioning
confidence: 98%
“…The direct excitation of Tm-O charge transfer band at 320 nm give rise to 1 G 4 → 3 H 6 and 1 D 2 → 3 F 4 transitions within the Tm ions with feeble energy transfer from Tm to Eu ions. Therefore, it can be concluded that the energy transfer between the codoped Tm 3+ and Eu 3+ is not sufficient in contrast to previously reported Tb 3+ → Eu 3+ energy transfer in Y 2 O 3 [9,15]. for example in solid state illumination, security-printing area, and other related areas.…”
Section: Luminescence Propertiesmentioning
confidence: 63%